Solve the equation 7 - 4x = x + 8.

First we add up all the 'x' terms. So the equation 7 - 4x = x + 8 becomes 7 - 4x - x = x +8 - x  => 7 - 5x = 8. Now we can do the same with the other terms. The equation now becomes 7 - 5x - 7 = 8 - 7 => - 5x = 1. The final step we must divide both sides by - 5 to solve for 'x'. Where we get x = -1/5.

Answered by Mira S. Maths tutor

3267 Views

See similar Maths 13 Plus tutors

Related Maths 13 Plus answers

All answers ▸

Solve algebraically the simultaneous equations: x^2 + y^2 = 25, y - 3x = 13


Find the roots of the following equation: x^2 + x - 6 = 0


Solve the following simultaneous equation: 3x+2y=20 and x+4y=20


Calculate 44 - (12 - 3^2)^2.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences